Analysis of Cardiac Amyloidosis Progression Using Model-Based Markers - Li, Wenguang; Lazarus, Alan; Gao, Hao; Martinez-Naharro, Ana; Fontana, Marianna; Hawkins, Philip; Biswas, Swethajit; Janiczek, Robert; Cox, Jennifer; Berry, Colin; Husmeier, Dirk; Luo, Xiaoyu (Frontiers in Physiology, 2020)
Deposition of amyloid in the heart can lead to cardiac dilation and impair its pumping ability. This ultimately leads to heart failure with worsening symptoms of breathlessness and fatigue due to the progressive loss of elasticity of the myocardium. Biomarkers linked to clinical deterioration can be crucial in developing effective treatments. However, to date progression of cardiac amyloidosis is poorly characterized, and there is an urgent need to identify key features that can predict the disease progression and cardiac tissue function. In this proof of concept study, we estimate a group of new markers based on mathematical models of the left ventricle derived from routine clinical magnetic resonance imaging and follow-up scans from the National Amyloidosis Centre at the Royal Free in London. Using mechanical modelling and statistical classification, we show that it is possible to predict disease progression. Our predictions agree with clinical assessments in a double-blind test in six out of the seven sample cases studied. Importantly, we find that multiple factors need to be used in the classification, which includes mechanical, geometrical and shape features. No single marker can yield reliable prediction given the complexity of the growth and remodelling process of diseased hearts undergoing high-dimensional shape changes. Our approach is promising in terms of clinical translation but the results presented should be interpreted with caution due to the small sample size.